Maternal and Child Determinants of Psychological Well-Being in Mothers Caring for Children with Chronic Conditions - Rinik Eko Kapti; Muhammad Is’haq Sulaiman; Nurona Azizah; Sholihatul Amaliya; Qori Ila Saidah; Lilik Supriati; Ridhoyanti Hidayah (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Caring for a child with a chronic condition imposes significant physical and psychological burdens on mothers, including increased stress, anxiety, depression, and difficulties balancing daily caregiving responsibilities with personal and social roles, which negatively impact their overall psychological well-being. This study aims to analyze the factors (maternal and child characteristics) associated with the psychological well-being of mothers who care for children with chronic conditions. A cross-sectional correlation design was used with 204 mothers of chronically ill children at Hospital in Malang City, selected through purposive sampling. The research instruments in this study are a questionnaire. Data analysis was performed using ordinal logistic regression. A p-value of less than 0.05 was considered statistically significant. Most mothers have moderate psychological well-being (72,1%). Multivariate analysis showed that mothers aged 26–35 years (OR = 0.113, p = 0.020), treatment duration under 1 year (OR = 5.551, p = 0.001), living in a village (OR = 0.221, p = 0.009), high family income (reference group, OR = 1.00), low obstacles to care (OR = 5.948, p = 0.009), good partner support (OR = 16.609, p = 0.002), good family support (OR = 6.062, p = 0.031), and good health worker support (OR = 6.965, p = 0.036) were significantly associated with increased maternal psychological well-being. Health workers can actively provide psychosocial support for mothers caring for children with chronic conditions, such as counseling. In addition, health workers must work with partners and families to create an emotionally supportive environment for mothers.